History of Economic Trade in Islam and Its Influence on International Relations Policy in the Arabian Peninsula - Yudha, Gesit; Aziz, Abdul; Arini, Isti (JURNAL TAPIS, 2024)
Abstract The Arabian Peninsula has a long history of trade, where the arrival of Islam introduced economic principles that emphasized justice and social responsibility, expanding trade networks, strengthening political stability, and influencing international relations. The aim of this study is to explore and analyze how the economic principles in Islam shaped and directed the development of trade in the Arabian Peninsula and the significant impact they had on international relations at the time. The research methodology employed in this study uses a literature review approach to gather, analyze, and synthesize relevant information. This study will begin by exploring various secondary sources, including history books, academic journal articles, and historical documents discussing Islamic economic trade principles as well as the political and social developments in the Arabian Peninsula. These sources will be selected based on their credibility and relevance to the research topic. The findings of this research indicate that trade has played a central role in the history of the Arabian Peninsula, from the pre-Islamic period to the Ottoman Empire. Cities like Mecca and Medina became vital trade centers, influencing the economy, politics, society, and culture. Trade became the foundation for international relations, enriching the economy, and impacting diplomacy and cultural development.